4(x+1)=2(x+20)

Simple and best practice solution for 4(x+1)=2(x+20) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+1)=2(x+20) equation:



4(x+1)=2(x+20)
We move all terms to the left:
4(x+1)-(2(x+20))=0
We multiply parentheses
4x-(2(x+20))+4=0
We calculate terms in parentheses: -(2(x+20)), so:
2(x+20)
We multiply parentheses
2x+40
Back to the equation:
-(2x+40)
We get rid of parentheses
4x-2x-40+4=0
We add all the numbers together, and all the variables
2x-36=0
We move all terms containing x to the left, all other terms to the right
2x=36
x=36/2
x=18

You can always share this solution

See similar equations:

| 3m+8=-5m-64 | | -k+5=3k-19 | | 5(a+2)-3(a-1)=3 | | X+8/x-2=1+4x/x-2 | | -7(a-4)=14 | | 7(x-10)=5x | | a?(?7a?3)=0 | | z^z^-8z=0 | | 3d-4d+8d=28 | | y-2/3=6 | | 2x+x+x+x=470 | | 4x-4=-5(7x-6)+83 | | (32/x)+6x=90 | | 32/x+6x=90 | | (-17-3r/2)=-19 | | (3-x)(4-x)-2=0 | | 1x^2-7x+2=-8 | | x4-15x2=16 | | f/4+75=158 | | 5x+13+4x+12=11x+3 | | (3x+5)/4-(2x-1)/3=2 | | 5x+13+4x+12+11x+3=180 | | 13f-72=760 | | 7f+49=434 | | 6m+21/2=33/2 | | (x+10)/2+3=2 | | x+10/2+3=2 | | 6x^2-9x-56.5=0 | | 33/2x-5-3=1/4 | | 5x+8-7x=15-17x+15x-7 | | 4(3x+4)=-4x+5 | | 6(4x-3)=9x+2 |

Equations solver categories